Effects of silicon and fungicides on the control of leaf and neck blast in upland rice - Seebold, KW; Datnoff, LE; Correa Victoria, Fernando J.; Kucharek, TA; Snyder, GH (Scientific Societies, 2004)
Silicon (Si) has been shown to suppress diseases of rice such as blast when applied to Si-deficient soils. In 1995 and 1996, Si was applied at 1,000 kg ha-1 to at two locations in eastern Colombia to determine if Si combined with reduced rates of fungicide could be used to manage leaf and neck blast effectively in upland rice. Two applications of edifenphos and three applications of tricyclazole were made at 0, 10, 25, or 100% of their labeled rates after amendment of soil with Si. At both locations, Si alone and Si combined with edifenphos reduced leaf blast severity by 22 to 75% when compared with nonamended, untreated controls, and suppression of leaf blast by Si alone was equal to or better than the full rate of edifenphos alone. Si alone suppressed neck blast as effectively or better than the full rate tricyclazole when severity was low; however, when severity was higher, a 10% rate of tricyclazole was needed in addition to Si. No differences in yield were observed between Si without fungicides and fungicides (full rate) without Si. Applications of Si made in 1995 had significant residual activity in terms of disease control and yield in 1996. The application of Si to Si-deficient soils may permit the use of reduced rates of fungicide to manage leaf and neck blast in upland rice.